Running after cycling induces inter-limb differences in muscle activation but not in kinetics or kinematics - Jacques, T.; Bini, R.; Arndt, A. (Journal of Sports Sciences, 2021)
Overuse injuries are a common problem to triathletes` population. Overuse injuries may arise from inter-limb biomechanical differences during running, but the literature lacks information regarding inter-limb differences in triathletes. In this study inter-limb differences were investigated in injury-free triathletes during the running portion of a simulated cycle-run transition. Thirteen triathletes performed a 5 km run preceded by a 20 min cycling trial at 70% of maximal power output. During the Start, Mid and End stages of running, kinetic, kinematic and muscle activation variables were compared between the preferred and non-preferred limbs across the stance phase. A statistical parametric mapping analysis showed no differences between limbs when considering kinetic and kinematic variables (p > 0.05, ES<0.60). A lower soleus activation was observed in the preferred limb (p < 0.05, ES>0.60) from 53.40-75.9% of the stance phase at the End stage of running. In conclusion, inter-limb differences in kinetic or kinematic variables may not represent a risk for overloading in triathletes. However, inter-limb differences in triceps surae activation during running after cycling may represent one potential factor leading to overuse injuries in triathletes and should be further investigated.